The impact of double mediation on market performance using information communication technology and market orientation - Moch. Rizky Indra Pratama (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2020)
Market performance is important to the company's development. This study examines the determinant factors of market performance through information and communication technology (ICT). The probability and simple random sampling methods were used to determine the sample. Furthermore, the research instrument was the questionnaire distributed personally to the respondents. The results show that the market performance of used car showroom MSMEs in the Malang was determined both directly and indirectly by information quality, eReadiness, use of ICTs, and market orientation, which is more dominant. The use of ICTs and market orientation fully and partially mediates the information quality and eReadiness on market performance, respectively.